2021
DOI: 10.1002/mabi.202100390
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cell Loading of Recombinant Spider Silk Based Bioinks on Gelation and Printability

Abstract: Printability of bioinks encompasses considerations concerning rheology and extrudability, characterization of filament formation, shape fidelity, cell viability, and post-printing cellular development. Recombinant spider silk based hydrogels might be a suitable material to be used in bioinks, that is, a formulation of cells and materials to be used for bioprinting. Here, the high shape fidelity of spider silk ink is shown by bioprinting the shape and size of a human aortic valve. Further the influence of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…The recombinant spider silk variant eADF4­(C16) consists of 16 repeats of the so-called C-module, inspired by the repetitive core domain of the natural Araneus diadematus fibroin 4, and was genetically modified with the integrin-binding peptide RGD improving the interaction with cells and with the integrin-binding inactive RGE as a control . As eADF4­(C16)-based proteins could be processed into physically cross-linked, nano-fibrillar hydrogels without the need of additional cross-linking agents, encapsulation and cultivation of cells inside these gels is possible . Additionally, due to their viscoelastic properties and shear-thinning behavior, 3D bioprinting of acellular hydrogels and bioinks made of spider silk proteins together with cells could be conducted. , Furthermore, it has been previously shown that different biologicals and drugs could be encapsulated inside and released from recombinant spider silk hydrogels with their activity maintained. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recombinant spider silk variant eADF4­(C16) consists of 16 repeats of the so-called C-module, inspired by the repetitive core domain of the natural Araneus diadematus fibroin 4, and was genetically modified with the integrin-binding peptide RGD improving the interaction with cells and with the integrin-binding inactive RGE as a control . As eADF4­(C16)-based proteins could be processed into physically cross-linked, nano-fibrillar hydrogels without the need of additional cross-linking agents, encapsulation and cultivation of cells inside these gels is possible . Additionally, due to their viscoelastic properties and shear-thinning behavior, 3D bioprinting of acellular hydrogels and bioinks made of spider silk proteins together with cells could be conducted. , Furthermore, it has been previously shown that different biologicals and drugs could be encapsulated inside and released from recombinant spider silk hydrogels with their activity maintained. , …”
Section: Introductionmentioning
confidence: 99%
“…As eADF4­(C16)-based proteins could be processed into physically cross-linked, nano-fibrillar hydrogels without the need of additional cross-linking agents, encapsulation and cultivation of cells inside these gels is possible . Additionally, due to their viscoelastic properties and shear-thinning behavior, 3D bioprinting of acellular hydrogels and bioinks made of spider silk proteins together with cells could be conducted. , Furthermore, it has been previously shown that different biologicals and drugs could be encapsulated inside and released from recombinant spider silk hydrogels with their activity maintained. , …”
Section: Introductionmentioning
confidence: 99%
“…The majority of materials used for cell patterning are based on the use of synthetic polymers specifically tailored to the selected patterning technique, especially when immobilization of biologically active components is required. , As a result of this customization, these materials are chemically different from the bulk materials used in tissue engineering and implants in general, making it difficult to directly link cell responses between microscopic and bulk platforms. In the case of the recombinant spider silk protein, the fibrous nature of bulk hydrogels, reflecting the ECM matrix, has become the basis for biofabrication approaches in tissue engineering. ,, Here, we applied spider silk self-assembly using the fibrous, hydrogel-like morphology that persists on the surface , to expose specific biotargeting functions represented by DNA interactions as a model. Moreover, any insights gained on the microstructured platforms based on the presented nanohydrogels will facilitate and accelerate the transfer of knowledge toward bulk hydrogels suitable for 3D printing of scaffolds or coatings of implants.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the recombinant spider silk protein, the fibrous nature of bulk hydrogels, 59 reflecting the ECM matrix, has become the basis for biofabrication approaches in tissue engineering. 39,60,61 Here, we applied spider silk self-assembly using the fibrous, hydrogel-like morphology that persists on the surface 41,42 to expose specific biotargeting functions represented by DNA interactions as a model. Moreover, any insights gained on the microstructured platforms based on the presented nanohydrogels will facilitate and accelerate the transfer of knowledge toward bulk hydrogels suitable for 3D printing of scaffolds or coatings of implants.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] Using chemically modified surfaces with the protein [31] or ultrathin nanofilms thereof, [32] the spider silk nanofibrils assembled on top into immobilized physically crosslinked networks, which displayed swelling and softening in the water, that is, properties similar to the bulk spider silk hydrogels. [33,34] The nanofibrillar nature of these nanohydrogels enabled a higher modification density and greater substrate accessibility compared to monolayers, whilst the mild aqueous self-assembly conditions in combination with the mechanical and chemical robustness of the nanohydrogels provided excellent scaffolds for embedding sensitive components such as enzymes and aptamers. [32] Spider silk proteins could be modified using both chemical [32,35] and genetic methods.…”
Section: Introductionmentioning
confidence: 99%